Enhancing the microstructure and strength gain of sustainable cement binders - Lin, Shiyi (2017)
Portland Cement (PC) is known to be the most popular binder in the construction industry. However, there is global concern about the environment impacts of PC due to the high energy demand and the high emission of carbon dioxide. There is a demand for an environmental friendly alternative to PC. In this experimental investigation conducted on various composition of sample is to find out the effects of different environments on the mechanical properties of reactive Magnesium Oxide (MgO) based samples against PC based samples. A total of three different design ratios of MgO sample will be subjected to 4 different durability environments testing and the highest initial durability of MgO design ratio will be remade using PC as the binder. All samples are cured through carbonation and constant temperature. Concurrently, porosity testing will be conducted through oven drying process to weigh the drop in water mass to determine the decrease of porosity in four different environments. This paper presents the result of two main aspects: durability characteristic properties of MgO-based and PC based and porosity of MgO-based. X-ray Powdered Diffraction (XRD), Scanning Electron Microscope (SEM) and Themogravimetric Analysis (TGA) were used to evaluate the difference in testing condition and duration. The result demonstrated that an increase of fine aggregate may have contributed to the high initial strength of MgO than PC due to the formation of hydromagnesite, nesquehonite and magnesite. However, the studies also showed that there is an increase of porosity with higher fine aggregate present in the sample and that a direct relation of harsher environments will increase the formation of brucite over a longer testing period.